Collaborative survival in the city: Envisioning alternative urban futures through Black agrarian praxis - Lindemann, Justine (Frontiers in Sustainable Food Systems, 2023)
Urban inhabitants exist within hybrid spaces of continual transformation and metabolism where human labor is woven into the work of the trees, the grass, the water cycle. The built environment – concrete, houses, skyscrapers – butts up against urban riparian zones and wetlands. The postindustrial landscape exposes both the possibilities and the limits of building resilience in the context of constant metabolism and change. This article asks about the potential for collaborative survival in these spaces of deindustrialization, where the abundance of so-called vacant parcels represent a pathway toward more self-determined food systems and the potential for reimagined urban futures. I play with the concept of collaborative survival to consider a plurality of epistemologies, knowledge systems, and traditions, as well as histories and geographies of exclusion that contribute to this reimagining. I examine the work of Black gardeners and farmers in Cleveland, OH as an example of collaborative survival: their work within a changing environment to grow food for themselves and their community, producing the city around them as a socio-ecological hybrid. Urban food production, in this case, serves as a praxis and a knowledge frame for liberation and emancipation. This paper explores urban agrarianism among Black residents in light of two historical moments that have deeply impacted Cleveland, and that I argue have shaped and informed Black agrarian praxis and growers' urban imaginaries. Collaborative survival recognizes that processes of urban development are ongoing and immanent and contests developmentalist narratives that marginalize epistemologies embracing alternative urban futures. Examining Black growers' experiences with attention to a framing around survival and resilience highlights the continuity of structural and systemic racism and violence against Black and brown bodies, as well as the innovations that individuals and groups deploy to contest that violence.